NICHE OF PRASUGREL AMONG OTHER PLATELET P2Y12-RECEPTOR INHIBITORS - P. S. LAGUTA; E. P. PANCHENKO («REMEDIUM GROUP» Ltd., 2017)
Platelet P2Y12-receptor inhibitors are ranked 2nd in terms of administration frequency among antiplatelet agents (after acetylsalicylic acid). Administration of such drugs is mandatory in conditions characterized by increased activation of platelets, which, above all, include acute coronary syndrome and percutaneous coronary interventions. The use of clopidogrel, the most famous and commonly used today representative of P2Y12 receptor inhibitors, does not always result in reducing a risk of thrombotic complications.The new generation representatives of the of P2Y12 receptor inhibitors (prasugrel, ticagrelor, cangrelor) showed their advantage over clopidogrel in the large-scale studies and are expected to improve the treatment situation not only in patients with acute coronary syndrome and after percutaneous coronary interventions, but also in other high-risk groups.